Physiological Changes In Spirometric Parameters During Pregnancy In Iraqi Women - Al-Nuamii, Salman H.; Al-Jubouri, Adnan M.; Sultan, Kasim M.; Mohammed, Ammar K.; Hamandi, Zaid M.A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: The events in pregnancy elicit one of the best examples of selective anatomical, physiological and biochemical adaptations, with profound changes in respiratory physiology. The changes in respiratory physiology are due to increased size of the fetus with advance gestation which constitutes a mechanical impediment to normal process of ventilation. .Patients and methods: This study started from the 1st of Nov. 2009 till the 30th of Oct. 2010. pregnant women aged (16-44 years) of different weight, height and different conception from 1st, 2nd, 3rd trimester and post term were included. Spirometry was performed in Baghdad teaching hospital( pulmonary function unit) . Result: FEV1/FVC ratio was found to be higher in the studied group as compared to the control group. The decrease in forced expiratory volume in one second (FEV1) with pregnancy is not of such amplitude as the decrease in forced vital capacity (FVC), so that the FEV1/FVC ratio was seen to increase. Decrease in FEV1, forced expiratory flow rate (FEF 0.12-0.25, 0.25-0.75) and peak expiratory flow rate (PEFR). Conclusions: This study informed that FEV1, FVC, (FEFR 0.12 -0.25, 0.25 -0.75) and peak expiratory flow rate values decreased during each stage of pregnancy.